Manufacture and Characterisation of Silicalite Monoliths - L.Y. Lee; S.P. Perera; B.D. Crittenden; S.T. Kolaczkowski (Adsorption Science & Technology)
Multichannel monoliths containing up to 90% silicalite by weight and with cell densities up to 28 cells/cm 2 , wall thicknesses down to 0.6 mm and an overall diameter of 40 mm have been prepared from silicalite powder and sodium bentonite (as a binder) by the unit operations of paste preparation, extrusion, drying and firing. The manufactured monoliths, which show good strength, retain the crystal structure and micropore size of the source silicalite powder, and adsorption measurements made by using a dynamic flow system confirm that the monoliths exhibit an equilibrium performance broadly similar to that of commercial silicalite pellets. In addition, the manufactured monoliths possess a higher macroporosity than the commercial pellets. Regeneration of the monoliths was found to be possible at mildly increased temperature. These features augur well for the recovery and/or separation of organic compounds in simple pressure swing and thermal swing processes.